Angiotensin receptor agonistic autoantibodies induce pre-eclampsia in pregnant mice - Zhou, Cissy C (2008)
Pre-eclampsia affects approximately 5% of pregnancies and remains a leading cause of maternal and neonatal mortality and morbidity in the United States and the world(1,2). The clinical hallmarks of this maternal disorder include hypertension, proteinuria, endothelial dysfunction and placental defects. Advanced-stage clinical symptoms include cerebral hemorrhage, renal failure and the HELLP (hemolysis, elevated liver enzymes and low platelets) syndrome. An effective treatment of pre-eclampsia is unavailable owing to the poor understanding of the pathogenesis of the disease. Numerous recent studies(3–5) have shown that women with pre-eclampsia possess autoantibodies, termed AT(1)-AAs, that bind and activate the angiotensin II receptor type 1a (AT(1) receptor). We show here that key features of pre-eclampsia, including hypertension, proteinuria, glomerular endotheliosis (a classical renal lesion of pre-eclampsia), placental abnormalities and small fetus size appeared in pregnant mice after injection with either total IgG or affinity-purified AT(1)-AAs from women with pre-eclampsia. These features were prevented by co-injection with losartan, an AT(1) receptor antagonist, or by an antibody neutralizing seven–amino-acid epitope peptide. Thus, our studies indicate that pre-eclampsia may be a pregnancy-induced autoimmune disease in which key features of the disease result from autoantibody-induced angiotensin receptor activation. This hypothesis has obvious implications regarding pre-eclampsia screening, diagnosis and therapy.